Local Wisdom and Laboratory Experiment-Based Extension Booklet Development for Wadi Makers of Elementary-Educated and Dropout Society in Central Kalimantan (Jurnal Pendidikan IPA Indonesia, 2020)
Wadi is one of traditionally fermented food types using basic materials of fish, salt, and lumu. As nutritive traditional food, wadi quality needs to be developed and maintained through social education. Wadi production innovation has not been done yet by the wadi makers since their information is limited on production techniques for better quality wadi. To promote local wisdom conservation, non-formal education for low educated-wadi makers is needed using simple media. Laboratory experiment and local wisdom-based booklet development is intended to broad their mind and skill in wadi production in the rural areas of Central Kalimantan. This development followed the model of Peck (1988). It contained non-formal product oriented-education materials for the wadi makers. The booklet has been validated by experts in community education, biotechnology, and learning media, and applied to wadi producing communities. Assessment instruments for booklet validation refer to non-textbook assessment instruments (enrichment books). The results showed that the booklet could be well accepted by the users and possessed very good criteria of understanding and readability value.